4G/5G Promoter PAI-1 Gene Polymorphism Is Associated with Plasmatic PAI-1 Activity in Italians: A Model of Gene-Environment Interaction - Burzotta, Francesco; Castelnuovo, Augusto Di; Amore, Concetta; D’Orazio, Andria; Bitondo, Rosa Di; Donati, Maria Benedetta; Iacoviello, Licia (Thrombosis and Haemostasis, 1998)
The PAI-1 gene promoter 4G/5G polymorphism was found to be associated with plasma PAI-1 activity in Northern and Central Europe populations, but no data are available on the association between this polymorphism and PAI-1 levels in Southern Europe countries (such as Italy) where the incidence of ischemic disorders is lower. This study shows that among populations with different incidence of atherothrombotic disorders the 4G/5G PAI-1 gene promoter polymorphism has the same importance in the regulation of plasma PAI-1 activity.Moreover, we have analysed some gene-environmental interactions: the correlation between PAI-1 and cholesterol in non dyslipidemic subjects and the correlation between PAI-1 activity and tryglicerides in dyslipidemic subjects differed according to the 4G/5G genotype class. Thus, our findings suggest that, among subjects with or without metabolic disorders such as dyslipidemia, completely different gene-environment interactions may occur.